A palladium-hinged organometallic square with a perfect-sized cavity for the encapsulation of three heteroguests. Issue 99 (28th November 2019) - Martínez-Agramunt, Víctor; Peris, Eduardo
Abstract : A nanometer-sized tetrapalladium metallosquare with a pyrene-bisimidazolylidene ligand was found to display a perfect-sized cavity for the encapsulation of three heteroguests, enabling the formation of quintuple D–A–D–A–D stacks. Abstract : A nanometer-sized tetrapalladium metallosquare with a pyrene-bisimidazolylidene ligand was found to display a perfect-sized cavity for the encapsulation of three heteroguests, enabling the formation of quintuple D–A–D–A–D stacks. The encapsulating properties of the metallosquare are clearly determined by the presence of the pyrene panels, which endow the metallosquare with a three-dimensional shape, and also behave as effective antennae for π-stacking interactions.